Enhancing the Speaking Skills of Intermediate BIPA (Bahasa Indonesia untuk Penutur Asing) Learners through Routines and Patterns - Zaka, Istifatun (LP2M Institut Agama Islam Negeri (IAIN) Kediri, 2024)
Enhancing the speaking skills of BIPA learners can be effectively achieved through the implementation of routines and patterns. However, this is often not paid attention to in foreign language learning, including BIPA, because it is directly at the creative language stage. For this reason, research is needed on whether foreign speakers' Indonesian speaking skills will improve if the learning process is carried out through routines and patterns. This qualitative descriptive study investigates the instructional environment of BIPA students at Yogyakarta State University, with a focus on the Yunan class. Data were collected from interactions between the instructor and BIPA students. The findings indicate that the use of routine and patterned expressions by instructors facilitates implicit language acquisition, allowing learners to internalize Indonesian through structured classroom routines. These routines and patterns play a crucial role in fostering and maintaining social interactions and optimizing communicative competence in Indonesian.